Kasih Persaudaraan sebagai Relasionalitas Masyarakat yang mengenal Allah: Suatu Teologi Bermasyarakat berdasarkan 1 Yoh 4:7-21 - Pasi, Gregorius (Sekolah Tinggi Pastoral IPI Malang, 2025)
One of the dangers to watch out for in midst of the vibrant religious life is the tendency to limit the significance of religion to spiritual life alone and ignore its significance for public life. This study aims to articulate the inspiration that Christian faith can provide for social life. With this inspiration, Christians can avoid the tendency to domesticate God in the private sphere. To achieve this goal, this research uses a qualitative method by conducting a critical reading of related literature. The results of the critical reading are elaborated by following the procedure of contextual theology proposed by Stephen B. Bevans, namely the dialectic between context and Scripture (and Tradition). Through this elaboration, it was found that the nature of society is relation and being in a society means relating. The relationality of a society that knows God is brotherly love that founded on the relationality of Trinitarian God. The essence of the love relationality of the Trinity is the perichoretic relationship of